Zinc(II) complexes with potent cyclin-dependent kinase inhibitors derived from 6-benzylaminopurine: synthesis, characterization, X-ray structures and biological activity - Trávníček, Zdeněk; Kryštof, Vladimír; Šipl, Michal (Journal of inorganic biochemistry, 2006)
The synthesis, characterization and biological activity of the first zinc(II) complexes with potent inhibitors of cyclin-dependent kinases (CDKs) derived from 6-benzylaminopurine are described. Based on the results following from elemental analyses, infrared, NMR and ES+MS (electrospray mass spectra in the positive ion mode) spectroscopies, conductivity data, thermal analysis and X-ray structures, the tetrahedral Zn(II) complexes of the compositions [Zn(Olo)Cl(2)](n) (1), [Zn(iprOlo)Cl(2)](n) (2), [Zn(BohH(+))Cl(3)] x H(2)O (3) and [Zn(iprOloH(+))Cl(3)] x H(2)O (4) have been prepared, where Olo=2-(2-hydroxyethylamino)-6-benzylamino-9-methylpurine (Olomoucine), iprOlo=2-(2-hydroxyethylamino)-6-benzylamino-9-isopropylpurine (i-propyl-Olomoucine), Boh=2-(3-hydroxypropylamino)-6-benzylamino-9-isopropylpurine (Bohemine). The 1D-polymeric chain structure for [Zn(Olo)Cl(2)](n) (1) as well as the monomeric one for [Zn(BohH(+))Cl(3)] x H(2)O (3) and [Zn(iprOloH(+))Cl(3)] x H(2)O (4) have been revealed unambiguously by single crystal X-ray analyses. The 1D-polymeric chain of 1 consists of Zn(Olo)Cl(2) monomeric units in which the Zn(II) ion is coordinated by two chlorine atoms and one oxygen atom of the 2-hydroxyethylamino group of Olomoucine. The next monomeric unit is bonded to Zn(II) through the N7 atom of a purine ring. Thus, each of Zn(II) ions is tetrahedrally coordinated and a ZnCl(2)NO chromophore occurs in the complex 1. The complexes 3 and 4 are mononuclear species with a distorted tetrahedral arrangement of donor atoms around the Zn(II) ion with a ZnCl(3)N chromophore. The corresponding CDK inhibitor, i.e., both Boh and iprOlo, is coordinated to Zn(II) via the N7 atom of the purine ring in 3 and 4. The cytotoxicity of the zinc(II) complexes against human melanoma, sarcoma, leukaemia and carcinoma cell lines has been determined as well as the inhibition of the CDK2/cyclin E kinase. A relationship between the structure and biological activity of the complexes is also discussed.
Keywords: chloridy; diferenční termická analýza; Differential Thermal Analysis; Humans; Molecular Structure; nádorové buněčné linie; Antineoplastic Agents; Spectrophotometry, Infrared; Magnetic Resonance Spectroscopy; Financing, Organized; Mass Spectrometry; Crystallography, X-Ray; protinádorové látky; organokovové sloučeniny; financování organizované; kinetin; puriny; Purines; Drug Screening Assays, Antitumor; Ligands; screeningové testy protinádorových léčiv; krystalografie rentgenová; inhibitory enzymů; hmotnostní spektrometrie; Kinetin; magnetická rezonanční spektroskopie; Cyclin-Dependent Kinases; spektrofotometrie infračervená; ligandy; Chlorides; lidé; Zinc Compounds; cyklin-dependentní kinasy; Organometallic Compounds; sloučeniny zinku; Enzyme Inhibitors; Cell Line, Tumor; molekulární struktura